2007
DOI: 10.1088/0031-9155/52/5/010
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of quantitative photoacoustic measurements of blood oxygenation in small vessels

Abstract: We investigate the feasibility of obtaining accurate quantitative information, such as local blood oxygenation level (sO2), with a spatial resolution of about 50 microm from spectral photoacoustic (PA) measurements. The optical wavelength dependence of the peak values of the PA signals is utilized to obtain the local blood oxygenation level. In our in vitro experimental models, the PA signal amplitude is found to be linearly proportional to the blood optical absorption coefficient when using ultrasonic transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 21 publications
2
88
0
Order By: Relevance
“…This question has been tackled for some specific scenarios. [11][12][13] Finally, photoacoustic techniques that have no imaging aspect are not covered here, so "gas phase" PA spectroscopy using a PA cell, which is a mature field in its own right, 14 is not described.…”
Section: What Is Not Covered In This Paper?mentioning
confidence: 99%
See 3 more Smart Citations
“…This question has been tackled for some specific scenarios. [11][12][13] Finally, photoacoustic techniques that have no imaging aspect are not covered here, so "gas phase" PA spectroscopy using a PA cell, which is a mature field in its own right, 14 is not described.…”
Section: What Is Not Covered In This Paper?mentioning
confidence: 99%
“…This implies that a relative measurement of the absorption coefficient, Kμ a;blood ðλÞ, will be sufficient to determine sO 2 as long as the multiplicative factor K does not depend on wavelength. 12 To use the amplitudes of PA signals as relative measurements of μ a , it is necessary to find a scenario in which the constant K, which for PA will be K ¼ΓΦ, is independent of wavelength. This is not true in general, in fact it is rarely true, and assuming it to be so 64 is likely to result in significant errors in sO 2 estimates.…”
Section: Blood Oxygen Saturationmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Maslov et al [10] and Zhang et al [11] have demonstrated exquisite images of subcutaneous microvasculature using dark-field confocal photoacoustic microscopy (PAM), a raster-scanning-based reflection geometry imaging system. Unique to photoacoustic methods is the ability to image blood oxygen saturation as well as concentration of total hemoglobin [11][12][13]. Emerging photoacoustic methods are enabling molecular imaging in small animals, including imaging of gene expression [14] and cell receptors [15].…”
Section: Introductionmentioning
confidence: 99%